PEMBELAJARAN KOLABORATIF BERBASIS TEORI VYGOTSKY SEBAGAI SARANA INTERNALISASI NILAI IMAN DALAM PENDIDIKAN AGAMA KRISTEN - Elvianti Febe Makamban; Emarani Fensia; Ati' Taruk Lawa; Selsilia Bellang; Rosiani; Siti Rante (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2026)
Christian Religious Education (CRE) faces a significant challenge, namely how to lead students not merely to understand doctrine, but to genuinely internalize faith values in real life. This study aims to analyze how collaborative learning based on Vygotsky's theory can serve as a means of internalizing faith values in CRE. Using a qualitative approach with a systematic literature review, this research examines various relevant theological, educational-psychological, and pedagogical sources. Findings indicate that Vygotsky's social constructivism theory resonates strongly with the communal principles in Ecclesiastes 4:9-10, where meaningful social interaction not only optimizes cognitive achievement but also creates space for authentic internalization of faith values. Collaborative learning provides the social context needed so that faith values are not merely intellectually understood but lived, felt, and shared within the learning community. This research offers a conceptual contribution that can serve as the foundation for developing more transformative CRE learning practices.